Mencegah Terjadinya Karies Dengan Menyikat Gigi Yang Benar Dan Pengolesan Topikal Aplikasi Flour di UPT SPF SD Negeri Minasa Upa Kota Makassar - Annisa, Nurul; Qalbi, Astri Annur; Alfah, Siti; Rapiudin, Risman Abdi; Aini, Nur (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Elementary school age is an ideal time to increase knowledge in the field of dental and oral health such as promotive, preventive, curative and rehabilitative. Promotive and preventive efforts are basic efforts in health services which aim to improve health status and prevent the occurrence of disease, in this case dental and oral disease in children. Minimal forms of activities that can be carried out routinely in the school environment include dental health education/DHE (dental health education), mass tooth brushing, including applying fluoride to teeth. Fluorine has a mechanism of action as an anticaries, namely inhibiting demineralization, increasing remineralization, and inhibiting bacterial glycolysis. The aim of this community service activity is to prevent dental caries by brushing teeth correctly and applying topical fluoride applications to elementary school students who are susceptible to caries to prevent dental caries (caries prevention). Methods for implementing this activity include problem identification, problem solving plans, implementation of activities. This activity was carried out in January 2025 at UPT SPF SD Negeri Minasa Upa, Makassar City. Before administering fluoride, education is first provided regarding dental health with material on caries and the benefits of fluorine for dental health. After that, fluoride was given to 35 grade 6 elementary school students. The results obtained by the number of DMF-T in students were included in the good category (2.3), and the OHI-S examination results obtained a good score (1.4). Dental health education by prioritizing tooth brushing techniques and the use of fluoride toothpaste, healthy behavior and avoiding unhealthy eating habits and carrying out regular dental examinations.